QTMP, a Novel Thiourea Polymer, Causes DNA Damage to Exert Anticancer Activity and Overcome Multidrug Resistance in Colorectal Cancer Cells - Bai, Zhaoshi; Zhou, Qing; Zhu, Huayun; Ye, Xinyue; Wu, Pingping; Ma, Lingman (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is one of the most common malignancies, and multidrug resistance (MDR) severely restricts the effectiveness of various anticancer drugs. Therefore, it is necessary to develop novel anticancer drugs for the treatment of CRC patients with MDR. Here, quaternarized thiourea main-chain polymer (QTMP) is a kind of self-assembled nanoparticle with good water solubility. It is worth noting that QTMP is not a P-glycoprotein (P-gp) substrate and exhibits potent cytotoxic activity against CRC cells, including P-gp-mediated MDR Caco2 cells. Interestingly, ROS and RNS production were increased in a concentration-dependent manner in QTMP-treated HCT116, SW480 and Caco2 cells. Importantly, in these CRC cells, QTMP causes DNA damage by directly inserting into DNA or regulating ROS and/or RNS production; moreover, QTMP also induces caspase-dependent apoptosis via the overproduction of ROS and RNS. In summary, QTMP is a promising anticancer agent for CRC treatment, particularly for patients bearing P-gp-mediated MDR cancer cells. Moreover, this study also indicates that the design and synthesis of anticancer drugs based on thiourea polymers is promising and valuable, thereby offering a new strategy to address MDR, and provides reference resources for further investigations of thiourea polymers.